Estimation of body input force transmission change due to parts' modification using the impedance method under rolling excitation. (February 2019) - Kang, Yeon June; Song, David P; Ih, Kang Duck
This study aims to estimate the change in suspension to body input force transmission due to the softening of the connecting elastomer under rolling excitation. In this respect, the suspension coupled to a vehicle body via an elastomer bushing is modeled using point impedance. A numerical study is performed for achievable force reduction due to a softened bush under the influence of different impedance combinations for the suspension and the vehicle body. Following a numerical study, the proposed model is validated through empirical testing of McPherson strut type suspension in the lateral arm Y direction and multilink type rear suspension in the front mount X direction, which represent extremely stiff and extremely soft coupling cases for the suspension type, respectively. Due to the difficulties in measuring road-induced operational forces within an actual vehicle, a validation test is performed using a previously developed rig that enables direct measurement of the force without modifying the structure of the suspension. Additionally, the rig-measured force, which is potentially misleading due to the large deviation in stiffness between the rig and an actual vehicle, is investigated under varying combinations of suspension and bush stiffness.